Sustainable Tourism Practices and Revisit Intention: The Mediating Role of Tourist Satisfaction in Bali’s Award-Winning Tourism Village - Ivory Budi Darmo Tang; Stephanie Kezia; Serli Wijaya (Petra International Journal of Business Studies, 2026)
This study examines how tourists’ perceptions of sustainable tourism practices influence their satisfaction and intention to revisit in Penglipuran Village, Bali. A quantitative causal research design was employed using survey data collected from domestic tourists who had visited Penglipuran Village. A total of 180 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that tourists’ perceptions of sustainable tourism practices have a positive and significant effect on tourist satisfaction. Tourist satisfaction, in turn, significantly influences revisit intention. However, the findings indicate that sustainable tourism practices do not directly influence revisit intention. Instead, tourist satisfaction plays a significant mediating role in the relationship between sustainability perceptions and revisit intention. This study contributes to the sustainable tourism literature by providing empirical evidence that sustainability-related destination attributes influence tourist loyalty primarily through tourist satisfaction rather than through a direct behavioural mechanism. The study also provides insights into how sustainability practices shape tourist behaviour in the context of a cultural tourism village.